PENINGKATAN KEMAMPUAN TEKNIK DASAR FOREHAND PERMAINAN TENIS MEJA DENGAN METODE LATIHAN TERBIMBING MATA PELAJARAN PENJASKESDIKELAS XII IPA 3 SMA NEGERI 3 TEBING TINGGI - Bahrum Bahrum (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
This purpose of this research is to improving forehand  hit in table tennis through guided exercises method. This classroom action researchconducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class XII IPA 3 Senior High School State 3 Tebing Tinggi which amounted to 37 students. This study used a qualitative descriptive analysis technique. The results showed that the use of the guided exercise method can improve forehand  hitin table tennis, characterized by increased mastery learning students, namely pre-cycle (54,5%), the first cycle (72,97%), cycle II (86,48%) and complete learn the clasical equal to 86,48 %.Key Word :Guided exercise,table tennis, forehand